Technology-Based Performance Effectiveness in Supporting Employee Work Discipline in The Organizational Secretariat of Batu City - Adiwidjaja, Ignatius; Trihardiyanto, Willy; Prayogi, Wahyu (REFORMASI, 2025)
The purpose of this study was to determine the effectiveness of technology-based performance in supporting work discipline in the Organizational Section of the Batu City Regional Secretariat and to identify supporting and inhibiting factors in the implementation of this technology. This study applied a qualitative approach using descriptive methods. Data were collected through observation techniques, in-depth interviews, and documentation collection. Informants were selected using purposive sampling, involving the Head of the Organizational Section, staff from the organizational section, and employees at the location. The results showed that information technology, such as a fingerprint-based attendance system, the Srikandi application (mail administration), SUKMAE (online services), and E-Kinerja, significantly improved work discipline through real-time monitoring, transparency, and process efficiency. The quality and quantity of work increased with more effective time utilization, as well as employee independence in completing tasks. However, there were inhibiting factors such as limited technological infrastructure, unstable internet networks, and suboptimal budget allocation. The main supporting factors included employees' understanding of technology, application availability, and WiFi facilities from the government. The implementation of information technology was proven to be effective in improving work discipline through improving quality, quantity, and time efficiency. However, this success depends on infrastructure improvements, increased budgets, and ongoing training. This study recommends accelerating digitalization and synergizing between stakeholders to optimize technology in the future. Penelitian ini bertujuan untuk mengetahui efektivitas kinerja berbasis teknologi dalam mendukung disiplin kerja di Bagian Organisasi Sekretariat Daerah Kota Batu serta mengidentifikasi faktor pendukung dan penghambat dalam implementasi teknologi tersebut. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data dilakukan melalui teknik observasi, wawancara mendalam, dan dokumentasi. Informan ditentukan menggunakan teknik purposive sampling yang melibatkan Kepala Bagian Organisasi, staf Bagian Organisasi, serta pegawai pada lokasi penelitian. Hasil penelitian menunjukkan bahwa pemanfaatan teknologi informasi, seperti sistem absensi berbasis fingerprint, aplikasi Srikandi (administrasi persuratan), SUKMAE (layanan daring), dan E-Kinerja, terbukti efektif dalam meningkatkan disiplin kerja melalui mekanisme pemantauan secara real-time, peningkatan transparansi, dan efisiensi proses kerja. Penerapan teknologi tersebut berdampak pada peningkatan kualitas dan kuantitas kerja, pemanfaatan waktu yang lebih efektif, serta meningkatnya kemandirian pegawai dalam menyelesaikan tugas. Namun demikian, implementasi teknologi masih menghadapi sejumlah kendala, antara lain keterbatasan infrastruktur teknologi, ketidakstabilan jaringan internet, serta alokasi anggaran yang belum optimal. Adapun faktor pendukung utama meliputi pemahaman pegawai terhadap teknologi, ketersediaan aplikasi pendukung, serta fasilitas jaringan WiFi yang disediakan oleh pemerintah daerah. Secara keseluruhan, implementasi teknologi informasi terbukti efektif dalam meningkatkan disiplin kerja melalui peningkatan kualitas, kuantitas, dan efisiensi waktu kerja. Keberhasilan tersebut sangat bergantung pada peningkatan infrastruktur, dukungan anggaran, serta pelatihan berkelanjutan. Penelitian ini merekomendasikan percepatan digitalisasi dan penguatan sinergi antar pemangku kepentingan guna mengoptimalkan pemanfaatan teknologi di masa mendatang.